2007
DOI: 10.1152/physrev.00034.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Glucagon-like Peptide 1

Abstract: Glucagon-like peptide 1 (GLP-1) is a 30-amino acid peptide hormone produced in the intestinal epithelial endocrine L-cells by differential processing of proglucagon, the gene which is expressed in these cells. The current knowledge regarding regulation of proglucagon gene expression in the gut and in the brain and mechanisms responsible for the posttranslational processing are reviewed. GLP-1 is released in response to meal intake, and the stimuli and molecular mechanisms involved are discussed. GLP-1 is extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
2,494
8
48

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,703 publications
(2,601 citation statements)
references
References 358 publications
(376 reference statements)
51
2,494
8
48
Order By: Relevance
“…Glucagon like Peptide-1 (GLP-1) is released in response to a meal from the small intestine [299] and reduces food-intake both in animals and humans [289, 300for review]. As a central site of action is possible [301][302][303], it is of interest that both GLP-1 and the GLP agonist exendin-4 stimulate 5-HT release from hypothalamic synaptosomes [304].…”
Section: -Ht Interactions With Other Gastrointestinal Peptidesmentioning
confidence: 99%
“…Glucagon like Peptide-1 (GLP-1) is released in response to a meal from the small intestine [299] and reduces food-intake both in animals and humans [289, 300for review]. As a central site of action is possible [301][302][303], it is of interest that both GLP-1 and the GLP agonist exendin-4 stimulate 5-HT release from hypothalamic synaptosomes [304].…”
Section: -Ht Interactions With Other Gastrointestinal Peptidesmentioning
confidence: 99%
“…Katsuma et al [18] have shown that bile acids promote glucagon-like peptide-1 (GLP-1) secretion through the bile receptor GpBAR-1 in a murine entero-endocrine cell line. GLP1 agonists are used in the treatment of type 2 diabetes because of their insulin-stimulating effect on the pancreatic B Cell, the inhibition of gastric emptying and the central effect on apatite inhibition, resulting in weight loss [19] . GLP-1 is secreted by L cells that are found in the distal ileum, colon, and rectum.…”
Section: G-protein-coupled Receptorsmentioning
confidence: 99%
“…In addition, the physiology of the digestive system and its role in glucose and energy homeostasis are complex and yet incompletely understood. Over the last decades the study of GI physiology has advanced at cellular and molecular levels revealing roles for several GI factors in the regulation of energy and glucose homeostasis including gut hormones (14)(15)(16) bile acids (17,18), miocrobiota (19,20), neural signals (21), and intestinal nutrient sensing (7). Paradoxically, however, the understanding of how anatomical segments of the GI tract contribute to metabolic regulation remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%